Deconstructing ADAURA: It is Time to Forgo Adjuvant Platinum-Based Chemotherapy in Resected IB-IIIA EGFR+ NSCLC (Except with RB Alterations?) When Adopting Adjuvant Osimertinib - Zhang SS; Ou SI (Lung Cancer: Targets and Therapy, 2022)
Shannon S Zhang,1 Sai-Hong Ignatius Ou1,2 1University of California Irvine School of Medicine, Department of Medicine, Orange, CA, USA; 2Chao Family Comprehensive Cancer Center, Orange, CA, USACorrespondence: Sai-Hong Ignatius Ou, University of California, Irvine School of Medicine, Department of Medicine, 200 South Manchester Ave, Suite 400, Orange, CA, 92868, USA Email siou@hs.uci.eduAbstract: Adjuvant cisplatin-based chemotherapy is considered the standard of care for resected stage IB (tumor ≥ 4m)–IIIA non-small cell lung cancer (NSCLC). The ADAURA trial is a randomized placebo-controlled Phase III trial that demonstrated statistically significant improved disease-free survival (DFS) with the use of 3-years of adjuvant osimertinib in resected stage IB–IIIA NSCLC harboring epidermal growth factor receptor (EGFR) del 19 or L858R mutations. Subgroup analysis revealed that the DFS improvement with adjuvant osimertinib is independent of adjuvant chemotherapy in the primary analysis. A recent follow-up report suggested that adjuvant cisplatin-based chemotherapy provided no additional 2-year DFS improvement on top of adjuvant osimertinib regardless of stage (IB, II, or IIIA) and minimal numerical DFS benefit in stage II or IIIA resected EGFR+ NSCLC for those patients who did not receive adjuvant osimertinib. Here, we argue that if clinicians adopt the use of 3 years of adjuvant osimertinib in resected early-stage EGFR+ NSCLC, there is no role for adjuvant platinum-based chemotherapy. The use of adjuvant chemotherapy was balanced between the osimertinib and the placebo arms by stage even though adjuvant chemotherapy was not one of the three stratification factors (del 19 vs L858R; Stage IA vs II vs III; Asians versus non-Asian) in ADAURA. There may be a potential role of adjuvant cisplatin/vinorelbine in a small subgroup of EGFR+ NSCLC patients whose tumor harbors retinoblastoma (RB) gene alterations but requires further investigation.Keywords: ADAURA, osimertinib, EGFR mutation, resected NSCLC, adjuvant, platinum-based chemotherapy, cisplatin; disease-free survival